Different Explosive Strength and Physiological Demands Between Male and Female Basketball Teams - Altavilla, Gaetano; D’Isanto, Tiziana; Raiola, Gaetano; D’Elia, Francesca (Physical Education Theory and Methodology, 2023)
Background. The several types of running in the team sports such as basketball, soccer and rugby, vary according to physical characteristics and sports. In particular, in the basketball the running is characterized by continuous acceleration and deceleration phases, which entails greater energy expenditure. This study aimed to assess the strength decrease of the lower limbs and energy expenditure at different running conditions (n=4) with/without the ball during Linear running and Shuttle run (180°) in two groups (male: n=15; female: n=15). Materials and methods. Experimental approach required the following tests/devices: Squat Jump to assess the strength of the lower limbs before/after each test, and a portable Metabolimeter was used to assess the metabolic parameters. The T-test was used for independent samples and Two-way repeated measures ANOVA was used to assess the significant differences for each variable between each running conditions. Results. Initial hypothesis has been confirmed, showing a significantly different strength decrease in different running conditions (Linear Running and Shuttle run with and without ball) and between the two teams considered (male and female). In addition, different energy expenditure between the two groups increases even more during the running with the ball compared to running without the ball. Conclusions. The results of this study could be useful for coaches to optimize training with different training load related to gender and to the running conditions (with and without the ball), but also to optimize the work load of young players in relation to the abilities, skills and experiences of players.